How internal venture groups innovate Byron L. David finds that new-product ventures are most successful when they involve someone who is both the intrapreneur and the venture manager - David, Byron L.
Product innovation by internal venturing is influenced by the mode of venturing you choose and the relationship between intrapreneurs, venture managers and the R&D functions.
Three modes of internal corporate venturing (ICV) are identified-differentiated by the origin of the product concepts; the roles of R&D, intrapreneurs and venture managers and by the degree of their products' commercial success, technical performance, radicalness and marketing and technological diversification. The ICV products, in general were found to be more radical and to represent a greater degree of marketing diversification for the firm than products created solely by the firms' mainstream divisions or by independent small firms. The findings, which are based on a survey of 139 Fortune 500 companies, also show that the least successful ventures were those in which product concepts originated with R&D.
Keywords: Internal venture groups